2021
DOI: 10.3390/mi12030345
|View full text |Cite
|
Sign up to set email alerts
|

Optical Detection Methods for High-Throughput Fluorescent Droplet Microflow Cytometry

Abstract: High-throughput microflow cytometry has become a focal point of research in recent years. In particular, droplet microflow cytometry (DMFC) enables the analysis of cells reacting to different stimuli in chemical isolation due to each droplet acting as an isolated microreactor. Furthermore, at high flow rates, the droplets allow massive parallelization, further increasing the throughput of droplets. However, this novel methodology poses unique challenges related to commonly used fluorometry and fluorescent micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…Overall, thanks to the aforementioned advantages LEDs are currently the most used technology for dynamic detection of the droplets in micro-and millifluific setups. Fluorescent microscopy with the integrated Charge Coupled Device (CCD) sensors and CMOS sensors are still actively employed to offer spatial monitoring of the droplets-fluorescence over time [18] (Figure 1e). This has high relevance for the realization of the droplet-based digital Polymerase Chain Reactions (PCR) and next generation sequencing for monitoring of e.g.…”
Section: Optical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, thanks to the aforementioned advantages LEDs are currently the most used technology for dynamic detection of the droplets in micro-and millifluific setups. Fluorescent microscopy with the integrated Charge Coupled Device (CCD) sensors and CMOS sensors are still actively employed to offer spatial monitoring of the droplets-fluorescence over time [18] (Figure 1e). This has high relevance for the realization of the droplet-based digital Polymerase Chain Reactions (PCR) and next generation sequencing for monitoring of e.g.…”
Section: Optical Methodsmentioning
confidence: 99%
“…Figure 1. Complete system for (a) droplet processing, (b) generation, (c) storage, (d) sorting, and (e) image analysis.Adapted with permission from refs [18,19]…”
mentioning
confidence: 99%
“…The principle of the fluorescence counter is shown in Figure 2 a. The fluorescence counter typically consists of an excitation light source, objective lenses, dichroic mirrors, a microfluidic sample platform, a photodetector, and a data acquisition and processing unit [ 23 , 24 ]. As fluorescent particles pass through the optical window, they are excited by an appropriate wavelength of light, and the emitted light is detected by a photodiode and converted to electric signals [ 25 ].…”
Section: Optical-based Countersmentioning
confidence: 99%
“…Recent research has shown a growing interest in the development of high-throughput microfluidic counters [ 24 ]. To this end, Li et al [ 31 ] presented an optical flow cytometer (OFCM) for single-cell phenotype counting.…”
Section: Optical-based Countersmentioning
confidence: 99%
“…The primary factors driving this increased demand are the need to advance drug development, analysis, testing, and rapid diagnostic methods [1,2,3]. However, there are several challenges associated with achieving this automation, and the problem complexity is well-defined in our previous works [4,5] i.e. automation of chip design, sensor technology, light source, and fabrication processes.…”
Section: Introductionmentioning
confidence: 99%